Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12544-018-0318-4
|View full text |Cite
|
Sign up to set email alerts
|

Group decision making process for early stage evaluations of infrastructure projects using extended VIKOR method under fuzzy environment

Abstract: Purpose: This paper considers the evaluations of project alternatives at the early stages of infrastructure project developments. Although it is expected to make important decisions at project early stages, it is rarely possible to obtain reliable data for exact evaluations. To deal with low quality data and the existence of uncertainties, this paper extends the evaluation problem to the fuzzy environment. Methods: We propose group decision making process for early stage evaluations of infrastructure projects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 40 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Therefore, the VIKOR method is suitable for solving decision-making problems with conflicted and noncommensurable criteria (which means, with different units) or when there are quantitative and qualitative criteria. The VIKOR method has been applied on many occasions for selection of alternatives in infrastructures, as reflected in the literature [36][37][38][39][40]. For normalization, converting the criteria into dimensional variables, a linear function is used in the VIKOR method that does not depend on a function of value of criteria as in the case of TOPSIS method [21].…”
Section: Mcdm Methodsmentioning
confidence: 99%
“…Therefore, the VIKOR method is suitable for solving decision-making problems with conflicted and noncommensurable criteria (which means, with different units) or when there are quantitative and qualitative criteria. The VIKOR method has been applied on many occasions for selection of alternatives in infrastructures, as reflected in the literature [36][37][38][39][40]. For normalization, converting the criteria into dimensional variables, a linear function is used in the VIKOR method that does not depend on a function of value of criteria as in the case of TOPSIS method [21].…”
Section: Mcdm Methodsmentioning
confidence: 99%
“…The program package VIKOR, based on compromise programming, has been developed by Opricović [3,4] for the multicriteria ranking of alternative solutions. The use of VIKOR method for the evaluation of railway infrastructure alternatives was proposed in papers [5,6].…”
Section: Vikor Method: a Compromise Programming Toolmentioning
confidence: 99%
“…The final results of appropriate decisions on these problems reflect in the reduction of container transhipment costs. Decision problems in the aspect of layout design and operational process have been discussed in papers [1][2]. In contrast to the previous research, this paper considers the location problem of a rail-road transhipment yard.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive reviews of the use of the VIKOR method could be found in [12]; and of the use of the PROMETHEE method in [13]. The VICOR method is employed for transport research of the railway route selection, and the assessment of infrastructure design projects, [14]; the selection of the forklift unit for warehouse operation, [15]; in maritime transportation industry, [16]; for evaluation of infrastructure railway project, [17]. The WASPAS method is used for the evaluation of potential locations for roundabout construction, [18]; the examples of different applications, [19].…”
Section: Literature Reviewmentioning
confidence: 99%